Review of the Argentinean species of Pseudomicrocara Armstrong (Coleoptera: Scirtidae) - Libonatti, María Laura; Ruta, Rafał (Zootaxa, 2013)
The Pseudomicrocara Armstrong from Argentina are reviewed. In total, seven species are present: Pseudomicrocara angusta sp. nov., P. antarctica (Fairmaire) comb. nov., P. hieroglyphica sp. nov., P. inflexipenis sp. nov., P. livida (Fabricius), P. obliquata (Solier) comb. nov., and P. patagonica (Curtis) comb. nov. New provincial records are provided for several species. Pseudomicrocara obliquata, previously known only from Chile, is recorded from Argentina for the first time. Illustrations of habitus and genitalia as well as distributional data for all Argentinean species of Pseudomicrocara are provided.